Case Report: Three-year follow-up of TACE for recurrent undifferentiated pleomorphic sarcoma: sustained local control and no systemic progression - Chen, Xiangrui; Hu, Min; Hao, Chengluo; Ma, Limei; Han, Yunwei (Frontiers in Oncology, 2025)
We report a case of recurrent undifferentiated pleomorphic sarcoma (UPS) in the right calf of a 48-year-old female patient who had undergone initial surgical resection in February 2018. The patient underwent two sessions of transcatheter arterial chemoembolization (TACE) between June and July 2022. During the procedures, superselective catheterization of the tumor-feeding arteries via the posterior tibial artery was performed, followed by infusion of epirubicin and sequential embolization with lipiodol, 300-500 μm microspheres, and gelatin sponges. Post-procedural angiography confirmed complete vascular occlusion. Clinical and imaging follow-up demonstrated significant tumor necrosis (60-70%) at one month post-treatment with progressive tumor shrinkage and central liquefaction. The disease remained stable at six months without distant metastasis. While literature reports of TACE for advanced sarcomas show PFS of 6.3–21 months, our case achieved 36-month PFS in locally recurrent non-metastatic UPS—suggesting greater efficacy in earlier disease stages. During 36 months of follow-up, sustained local control was achieved without systemic progression. These findings suggest that for vascular-rich recurrent UPS when surgical resection is challenging, TACE represents a feasible locoregional therapeutic option.